Pola Hidup Sehat Dan Pengetahuan Penanganan Keluhan Vegetatif Pra Dan Menopouse Dengan Pendekatan Kebidanan-Akupuntur - Widia Shofa Ilmiah; Sulistiyah; Ikhwan Abdullah (CV. Multi Kreasi Media, 2024)
Pre-menopause is the period before perimenopause which is characterized by the beginning of decreased reproductive function until the appearance of vegetative complaints or other signs of menopause. Menopause is a biological stage of women, which is characterized by the cessation of menstruation after 12 consecutive months. The incidence of menopause in Indonesia on average occurs at the age of 45-55 years in 90% of women. About 5% will occur after age 55. Data from the Central Statistics Agency in 2021 when compared to the total population of Indonesia at the age of 40-45 years is 21.88% and the population of productive age between 15-64 years is 70.72% of the total population of 270.20 million people. The results of interviews with the head of the PKK and Mrs. RT 03 Mangliawan Village, District, Malang Regency that the partner's problem is the many vegetative complaints felt by PKK member mothers in the form of hot flushes, insomnia, dyspareunia, and osteoporosis as well as the habit of drinking less water. The purpose of this activity is to increase knowledge about healthy lifestyles and knowledge of handling pre-menopause and menopause vegetative complaints with obstetrics and acupuncture approaches. Method of Implementation of activities using pre-test and post-test techniques with interventions in the form of health promotion. Pamphlet and questionnaire instruments. The results of this activity showed that there was an increase in knowledge of healthy lifestyles (p = 0.001) and the level of knowledge of handling pre- and menopausal vegetative complaints (p = 0,000). This activity concludes that there is a success of health promotion activities by increasing knowledge of healthy lifestyles and knowledge of handling vegetative complaints in empowering family welfare of mothers.